Data mining, machine learning, and business intelligence - a case study on cryptocurrencies - Marinho, Felipe Israel; Adaniya, Mario Henrique Akihiko da Costa (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 39 No 76 (2023): Publicação Contínua, 2023)
This work aimed at the use of diverse techniques such as Data Mining, Machine Learning and graphic techniques using Business Intelligence tools for extracting, processing and analyzing data coming from social networks, more specifically in application message groups Telegram, in order to validate if we can verify correlation between the feelings that the users express in this social network and the price fluctuation of the Bitcoin cryptocurrency. The intention is to present a complete comparative analysis between the data coming from the Telegram social network with the scenario of higher price of this crypto-currency in December 2017. First, an exploratory research aimed at introducing several aspects of all technologies used in the development of this job will be displayed. The application of the survey will take place in real data coming from the social network Telegram. At the end we will have a comparative table using statistical models to find a correlation between the variables worked during the development and the research, which are sentimental analysis and the prices of the currencies.